0464 How do gender and jurisdiction interact with work disability duration?. (21st August 2017) - Macpherson, Robert; Koehoorn, Mieke; Quirke, William; Fan, Jonathan; Amick, Benjamin; Mustard, Cameron; Hogg-Johnson, Sheilah; Kraut, Allen; McLeod, Christopher
Abstract : Objectives: We examine whether gender differences in work disability duration were consistent across Canadian provinces and by length of work disability duration. Methods: Cohorts of injured workers in British Columbia (BC), Manitoba (MB) and Ontario (ON) were analysed using claim-level data for injuries occurring between 2007 and 2011. Work disability duration was measured using cumulative days that claims received work disability benefits during one-year post-injury. Extended Cox models provided hazard ratios (HR) and 95% confidence intervals (95% CI) to examine differences between women compared to men transitioning off work disability benefits and how this varied by length of work disability duration in each jurisdiction, adjusting for confounders. Results: In all three provinces, women transitioned off disability benefits slower initially (at 1 day, BC: HR: 0.90 [95% CI: 0.89–0.91], MB: HR: 0.89 [95% CI: 0.87–0.91], and ON: HR: 0.96 [95% CI: 0.95–0.97]) but in longer claims women transitioned off disability benefits faster (at 9 months, BC: HR: 1.10 [95% CI: 1.07–1.13]; MB: HR 1.14 [95% CI 1.08–1.21], and ON: HR: 1.03 [95% CI: 1.01–1.06]. This finding was consistent across different models by province and injury type. Conclusions: The persistent differences in work disability duration suggest that there may be underlying gender or sex differences in terms of recovery from work-related injury. Policies for the prevention and management of work injuries should be tailored to men's and women's specific needs and barriers. The timing of such interventions should be considered given the time-varying differences observed between men and women.